PUBLIC TRANSPORT PERSPECTIVES FOR 2030 IN BRAZIL: A PATH TOWARDS SUSTAINABLE MOBILITY - Delgado, Fernanda Camila Martinez [UNESP]; Jesus, Gessica Mina Kim [UNESP]; Furlan, Marcelo; Bezer, Barbara Stolte [UNESP] (RGSA- Revista de Gestao Social e Ambiental, 2022)
Objective: The objective of the study was to analyze projections that impact sustainable urban mobility for the year 2030 in small and medium-sized cities that use the bus as the main modal. Theoretical framework: The research brings perspectives to make urban mobility in small and medium-sized Brazilian cities more sustainable. Method: The Survey method was used; data collection through a questionnaire applied to public transport specialists in Brazil. In the data analysis, the calculation of the degree of agreement of the answers was used for 13 projections, in three aspects: probability of occurrence, business impact and the desire to occur. The averages of each category were also taken, plotted on a graph with X axis (probability of occurrence) and Y axis (impact on the transport sector). Results and conclusion: The results point to an increase in the use of semi-public transport, tariff changes and greater integration between the bus and more sustainable modes such as walking and cycling. For sustainable mobility, a greater interest in sustainability, investment in infrastructure, dedicated corridors and lanes, integration between modes, use of renewable energy and implementation of subsidy can be the key to environmental solutions. Research implications: The research contributed theoretically to the literature review and managerial and political questionnaire indicating the priority points for public and private investments. Originality/value: The research points out investment points to make urban mobility more sustainable and at the same time profitable for transport companies.
PERSPECTIVAS DO TRANSPORTE PÚBLICO PARA 2030 NO BRASIL: UM CAMINHO RUMO À MOBILIDADE SUSTENTÁVEL
Keywords: buses; public transport; sustainable development; sustainable urban mobility